Evaluasi Kelayakan Agregat Halus Campuran Beton Konstruksi Bangunan pada ASTM - Cangkung, Arnoldus Fredrik Otto; Caling, Claudius Lippershey B.; Gon, Kasmir; Sabu, Maria Kalista H.; Beyan, Eleonora Vilgia P.; Ihut, Karolina V. D.; Jo, Antonius A. (Politeknik Negeri Lhokseumawe, 2025)
A maximum Fine aggregate is one of the main components in concrete mixtures, playing a crucial role in improving density, strength, and workability in construction materials. This study aims to analyze the characteristics of fine aggregate from Tuke Nikit sand based on ASTM C33 standards, including tests for silt content, moisture content, specific gravity, water absorption, and particle gradation. The test results indicate that the average silt content is 1.73%, which is below the maximum limit of 3–5% according to ASTM C117. The average moisture content is 2.35%, which may affect the water-cement ratio in concrete mixtures. The average specific gravity is 2.35, which falls within the normal range; however, the high water absorption rate (7.43%) indicates a relatively high porosity. Gradation analysis shows that the sand meets ASTM C33 specifications and is classified as well-graded, making it suitable for use in building construction. Based on these findings, Tuke Nikit sand can be recommended as a viable fine aggregate for concrete mixtures, although moisture content and porosity control are necessary to maintain construction quality.